Analysis of Factors Influencing Students' Financial Analysis Skills with GPA as a Control Variable - Wahyu Febru Royen; Kathryn Sugara (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Higher education contributes significantly to developing students' financial analysis competencies, but the gap between academic achievement and practical skills remains a major challenge. This study was designed to analyze factors influencing students' financial analysis skills with Grade Point Average (GPA) as a control variable. This study used a quantitative approach with a survey method involving 415 active Accounting and Management student respondents from ten universities in Palembang City. Data were collected through a five-point Likert scale-based questionnaire and analyzed using multiple linear regression with the help of SPSS version 26. The research constructs consisted of understanding basic accounting concepts, financial management, the use of digital accounting technology as independent variables, financial analysis skills as dependent variables, and GPA as control variables. The results showed that the three independent variables had a positive and significant effect on financial analysis skills with an R Square value of 0.807. The use of digital accounting technology was the most dominant factor with a beta coefficient of 0.592, followed by financial management (beta 0.220) and understanding basic accounting concepts (beta 0.127). The Grade Point Average strengthened the relationship between the independent variables and financial analysis skills. In conclusion, the integration of digital literacy, conceptual competency, and financial management understanding is crucial for developing students' analytical skills in the digital age. Higher education institutions need to optimize their technology-based and practice-based curricula to prepare graduates who are competitive in the financial industry